A novel synthetic luteinizing hormone-releasing hormone (LHRH) analogue coupled with modified β-cyclodextrin: Insight into its intramolecular interactions - Kordopati, Golfo G.; Tselios, Theodore V.; Kellici, Tahsin; Merzel, Franci; Mavromoustakos, Thomas; Grdadolnik, Simona Golic; Tsivgoulis, Gerasimos M. (Biochimica et biophysica acta, 2015)
Cyclodextrins (CDs) in combination with therapeutic proteins and other bioactive compounds have been proposed as candidates that show enhanced chemical and enzymatic stability, better absorption, slower plasma clearance and improved dose–response curves or immunogenicity. As a result, an important number of therapeutic complexes between cyclodextrins and bioactive compounds capable to control several diseases have been developed. In this article, the synthesis and the structural study of a conjugate between a luteinizing hormone-releasing hormone (LHRH) analogue, related to the treatment of hormone dependent cancer and fertility, and modified β-cyclodextrin residue are presented. The results show that both the phenyl group of tyrosine (Tyr) as well as the indole group of tryptophan (Trp) can be encapsulated inside the cyclodextrin cavity. Solution NMR experiments provide evidence that these interactions take place intramolecularly and not intermolecularly. The study of a LHRH analogue conjugated with modified β-cyclodextrin via high field NMR and MD experiments revealed the existence of intramolecular interactions that could lead to an improved drug delivery. NMR in combination with MD simulation is of great value for a successful rational design of peptide–cyclodextrin conjugates showing stability against enzymatic proteolysis and a better pharmacological profile. [Display omitted] •A conjugate of a LHRH analogue and modified β-cyclodextrin was synthesized.•High field NMR spectroscopy and MD simulations were used as tools in our study.•Interactions between tryptophan, tyrosine and the cyclodextrin unit were observed.•Encapsulation of the tryptophan and tyrosine was partial and intramolecular.